2015
DOI: 10.11604/pamj.2015.22.4.6075
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and prognostic properties of TB-LAM among HIV-positive patients initiating ART in Johannesburg, South Africa

Abstract: While the diagnostic properties of the TB LAM urine assay (LAM) have been well-described, little is known about its predictive and prognostic properties at ART initiation in a routine clinic setting. We describe the predictive and prognostic properties of LAM in HIV-positive patients initiating ART at an urban hospital in Johannesburg, South Africa. Retrospective study of HIV-positive adults (>18 years) who initiated standard first-line ART between February 2012 and April 2013 and had a LAM test at initiation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In 2019, the WHO updated its guidelines to recommend outpatient LAM testing for anyone with a CD4 count of less than 100 cells/µL irrespective of symptoms [170]. While LAM testing has been shown to improve diagnostic yield for TB [171], it is unclear if it can detect cases not already suspected for TB, and small studies have shown it unable to predict either unmasking or paradoxical IRIS [121,172]. A novel LAM assay has increased sensitivity and thus might allow prevention of unmasking IRIS [123].…”
Section: Risk Factors and Preventionmentioning
confidence: 99%
“…In 2019, the WHO updated its guidelines to recommend outpatient LAM testing for anyone with a CD4 count of less than 100 cells/µL irrespective of symptoms [170]. While LAM testing has been shown to improve diagnostic yield for TB [171], it is unclear if it can detect cases not already suspected for TB, and small studies have shown it unable to predict either unmasking or paradoxical IRIS [121,172]. A novel LAM assay has increased sensitivity and thus might allow prevention of unmasking IRIS [123].…”
Section: Risk Factors and Preventionmentioning
confidence: 99%
“…Then we went over the text, and 95 studies were eliminated for various reasons. Finally, 67 articles with a total of 164 reports and 23727 samples were included 6 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , ...…”
Section: Resultsmentioning
confidence: 99%